2012
DOI: 10.1177/1754337112438305
|View full text |Cite
|
Sign up to set email alerts
|

Injury data from unhelmeted football head impacts evaluated against critical strain tolerance curves

Abstract: Concussion is a prevalent injury in collision and contact sports, but the biomechanics of concussion has mainly been assessed for helmeted head impacts. Concussion and no-injury cases had previously been reconstructed using rigid body simulations from a larger video database of unhelmeted head impact cases from Australian rules football, rugby union and rugby league. The KTH finite element human head model was used to simulate the 27 concussion and 13 no-injury cases, and the maximum principle strain levels in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 51 publications
0
14
2
Order By: Relevance
“…Visible brain lesions were noted in both translated and rotated groups but with a greater frequency and severity after rotation. Patton et al (2012) suggested rotational kinematics above 4500 rad/s 2 and 33 rad/s for peak resultant angular acceleration and maximum change in resultant angular velocity, respectively, to predict concussions involving loss of consciousness lasting longer than 1 min in rugby and Australian football impacts. Recently, Rowson et al (2012) recorded 57 concussions and a large number of sub-concussive impacts during the 2007–2009 collegiate American football season, and proposed 6383 rad/s 2 in rotational acceleration associated with 28.3 rad/s in rotational velocity to represent a 50% risk of concussion.…”
Section: Brain Injuries Primarily Induced By Rotational Kinematicsmentioning
confidence: 99%
“…Visible brain lesions were noted in both translated and rotated groups but with a greater frequency and severity after rotation. Patton et al (2012) suggested rotational kinematics above 4500 rad/s 2 and 33 rad/s for peak resultant angular acceleration and maximum change in resultant angular velocity, respectively, to predict concussions involving loss of consciousness lasting longer than 1 min in rugby and Australian football impacts. Recently, Rowson et al (2012) recorded 57 concussions and a large number of sub-concussive impacts during the 2007–2009 collegiate American football season, and proposed 6383 rad/s 2 in rotational acceleration associated with 28.3 rad/s in rotational velocity to represent a 50% risk of concussion.…”
Section: Brain Injuries Primarily Induced By Rotational Kinematicsmentioning
confidence: 99%
“…Images were generated using 3DSlicer from ATLAS-based anatomical representation in FreeSurfer (Zhang et al, 2018). 0.2 (Patton et al, 2012), MPS CC = 0.2 (Kleiven, 2007), and FS CC = 0.074 .…”
Section: Injury Metric Error Analysismentioning
confidence: 99%
“…Franceschini et al [38] have experimentally studied the mechanical behavior of human brain tissue at strain rates ranging between 0.0055 and 0.0093 s −1 . Although their results are valid to be employed for studies in quasistatic loading, those material properties have been used in many computational simulations of TBI at dynamic loads [39,40]. It was confirmed [16,41] that, in addition to selecting an appropriate constitutive model, using the material constants derived from a mismatched strain rate may considerably affect the validity of the results.…”
Section: Introductionmentioning
confidence: 99%